INVESTIGATION ON VOID FRACTION FOR TWO-PHASE FLOW PRESSURE DROP OF EVAPORATIVE R-290 IN HORIZONTAL TUBE (Jurnal Teknologi (Sciences & Engineering), 2016)
Two-phase flow boiling pressure drop experiment was conducted to observe its characteristics and to develop a new correlation of void fraction based on the separated model. Investigation is completed on the natural refrigerant R-290 (propane) in a horizontal circular tube with a 7.6 mm inner diameter under experimental conditions of 3.7 to 9.6 Â°C saturation temperature, 10 to 25 kW/m2 heat flux, and 185 to 445 kg/m2s mass flux. The present experimental data was used to obtain the calculated void fraction which then was compared to the predicted void fraction with 31 existing correlations. A new void fraction correlation for predicting two-phase flow boiling pressure drop, as a function of Reynolds numbers, was proposed. The measured pressure drop was compared to the predicted pressure drop with some existing pressure drop models that use the newly developed void fraction model. The homogeneous model of void fraction showed the best prediction with 2% deviation